The Relationship Between Smoking Habits And The Incidence Of Chronic Obstructive Pulmonary Disease (COPD) In Adult Males In The Working Area Of Public Health Center X - Sari Arie Lestari. B; Bachrudin Lain; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic disease that is a public health problem with a continuously increasing prevalence. Smoking is a major risk factor for COPD, especially in adult men. This study aims to determine the relationship between smoking and COPD incidence in adult men in the working area of Community Health Center X. This study used an analytical quantitative design with a cross-sectional approach. The study sample consisted of 60 adult male respondents, selected using a purposive sampling technique. Data were collected using a smoking habits questionnaire and COPD diagnosis data from medical records. Data analysis used the Chi- Square test. The results showed a p value = 0.001 (<0.05) which means there is a significant relationship between smoking habits and the incidence of COPD. The conclusion of this study is that smoking habits are closely related to the increasing incidence of COPD in adult men.